Junie B., first grader : boss of lunch - Park, Barbara; Brunkus, Denise (New York : Random House, 2002)
Junie, an outspoken, sometimes exasperating, first grader is thrilled when she is told she can help out in the school cafeteria.
"A Stepping Stone book."
School Library Journal, August 2002
Booklist, July 2002
Kirkus Review, May 2002
2.8
K-3
Keywords: Jones, Junie B. (Fictitious character) -- Fiction; Schools -- Fiction; School lunchrooms, cafeterias, etc. -- Fiction; Jones, Junie B. (Fictional character) -- Fiction; School stories; Food service -- Fiction